The Party System Practices Within a Presidential Government System Based on The 1945 State Constitution of The Republic Of Indonesia Before and After The Amendments - Pratama, Topan Yulia (UNISKA LAW REVIEW, 2023)
Political parties are considered democratic institutions expected to help build a stable and democratic government. Conversely, political parties are often considered to trigger government instability. This study aims to 1) discover the history of the party system within General Elections in Indonesia and 2) investigate the influence of the multiparty political structure implemented in the presidential system. This normative legal article uses a historical approach to describe the party system history of some presidents and the House of Representatives before and after the amendment of the 1945 Constitution. Afterward, each history will be compared to investigate the comparison of the President's power relationship with the House of Representatives before and after the amendment of the 1945 Constitution. The findings showed that 1) the party system before the amendment (hereafter, the New Order) benefited the ongoing government. The president had no problems with political support because the government party was always the party supporting the government with an absolute majority in parliament. In contrast, the party system after the amendment (hereafter, multiparty politics) is considered a solution to maintain stability and balance in the ongoing political system. The president had some difficulties getting majority support from parliament, thus coalition between the president and political parties is a form of compromise. 2) The impact of a multiparty system is that the president indirectly allows parties outside him to influence his power structure. In conclusion, the problems of the presidential and multiparty system can be resolved with an accommodative and compromise presidential style of government.